Застосування комплексної терапії у лікуванні синдрому гіпепролактинемії - Авраменко, Наталія Вікторівна; Грідіна, Ірина Борисівна; Нікіфоров, Олег Анатолійович; Разиграєва, Марина Олександрівна; Авраменко, Н. В.; Гридина, И. О.; Никифоров, А. А.; Разыграева, Н. А.; Avramenko, N. V.; Gridina, I. B.; Nikiforov, O. A.; Razygraeva, M. O. (Чорноморський національний університет ім. Петра Могили, 2019)
Синдром гіперпролактинемії залишається міжфаховою проблемою і є актуальним питанням по теперішній час. Він займає друге місце у структурі ендокринного безпліддя та невиношування вагітності. У сучасному ритмі життя стан хронічного стресу провокує зміну компенсаторної функції пролактину на патологічну. Кортизол підвищує андрогени та викликає депресію рівня лютеїнізуючого та фолікулостимулюючого гормону, що надалі проявляється у зменшенні синтезу естрадіола та прогестерону, зменшується чутливість тканини яєчників до гонадотропін релізінг гормону. Пролактин – як секундна стрілка годинника, миттєво реагує на стрес та запускає цілий механізм впливу на репродуктивну систему. За даними досліджень відомо, що жінки, які ведуть активний спосіб життя та працюють на відповідальній роботі мають більшу вірогідність виникнення гіперпролактинемії. Яка, у свою чергу, часто призводить від змін у молочній залозі, порушень менструального циклу до безпліддя та невиношування. На сьогодні препаратом вибору у лікуванні гіперпролактинемії є препарати агоністів дофамінових рецепторів, а саме – карбеголін. Доведена ефективність та безпека використання цих препаратів. У той же час у літературі недостатньо даних про тривалість збереження клініко-лабораторного ефекту після терапії агоністами дофамінових рецепторів. З метою проаналізувати ефективність комплексної та монотерапії, відстежити тривалість утримання рівня пролактину у межах референтних значень через 1 та 3 місяці лікування було обстежено 75 жінок репродуктивного віку, що страждали на безпліддя. Жінки були розподілені на три групи: у першій групі використовувався карбеголін з плазмаферезом, у другій – карбеголін з озонотерапією, а в третій – тільки медикаментозна терапія. Встановлено, що комплексне застосування немедикаментозних методів лікування впливає на збереження рівня пролактина у межах референтних значень більш тривалий проміжок часу, про що свідчить результати аналізів сироватки крові. Це значно підвищує позитивний прогноз у якості вагітності у пацієнток з функціональною гіперпролактинемією. Резюме. Синдром гиперпролактинемии остается междисциплинарной проблемой и является актуальным вопросом по настоящее время. Гиперпролактинемия занимает второе место в структуре эндокринного бесплодия и невынашивания беременности. В современном ритме жизни состояние хронического стресса провоцирует изменение компенсаторной функции пролактина в патологическую. Кортизол повышает андрогены и вызывает депрессию уровня лютеинизирующего и фолликулостимулирующего гормона, что в дальнейшем проявляется в уменьшении синтеза эстрадиола и прогестерона, уменьшается чувствительность ткани яичников к гонадотропин рилизинг гормону. Пролактин – как секундная стрелка часов, мгновенно реагирует на стресс и запускает целый механизм влияния на репродуктивную систему. По данным исследований известно, что женщины, которые ведут активный образ жизни и работают на ответственной работе имеют большую вероятность возникновения гиперпролактинемии. Которая, в свою очередь, часто приводит от изменений в молочной железе, нарушений менструального цикла до бесплодия и невынашивания. На сегодня препаратом выбора в лечении гиперпролактинемии являются препараты агонистов дофаминовых рецепторов, а именно - карбеголин. Доказана эффективность и безопасность использования этих препаратов. В то же время в литературе недостаточно данных о продолжительности сохранения клинико-лабораторного эффекта после терапии агонистами дофаминовых рецепторов. С целью проанализировать эффективность комплексной и монотерапии, отследить длительность удержания уровня пролактина в пределах референтных значений через 1 и 3 месяца лечения было обследовано 75 женщин репродуктивного возраста, страдающих бесплодием. Женщины были разделены на три группы: в первой группе использовался карбеголин с плазмаферезом, во второй – карбеголин с озонотерапией, а в третьей – только медикаментозная терапия. Установлено, что комплексное применение немедикаментозных методов лечения влияет на сохранение уровня пролактина в пределах референтных значений более длительный промежуток времени, о чем свидетельствует результаты анализов сыворотки крови. Это значительно повышает процент положительного прогноза в качестве беременности у пациенток с функциональной гиперпролактинемией. Abstract. Hyperprolactinemia is due to a major problem and current nutrition at the current hour. The loan is different from the endocrine-free structure and the miscarriage. At the current rhythm of life, the chronical stress provokes the compensatory function of prolactin for pathology. Cortisol raises androgens and reduces Luteinizing and Follicle-stimulating hormones, which should be manifested in the decreased synthesis of estradiol and progesterone, changes in the sensitivity of the tissue to the growth of hormone-releasing hormone. Prolactin instantly responds to stress and triggers a whole mechanism of influence on the reproductive system. According to the research, the women who lead active lifestyle and work in responsible jobs have a greater likelihood of hyperprolactinemia. This often leads to problems ranging from changes in the mammary gland, menstrual irregularities to infertility and miscarriage. The difficulty in diagnosing hyperprolactinemia is primarily because it usually occurs when clinical symptoms appear. Today, the drug of choice in the treatment of hyperprolactinemia is dopamine receptor agonist drugs, named cabergoline. The effectiveness and safety of using these drugs was proved. At the same time, there is insufficient data in the literature about the duration of the preservation of clinical and laboratory effects after treatment with dopamine receptor agonists. Material and methods. We examined 75 women of reproductive age who became infertile in order to analyze the effectiveness of complex and monotherapy, and to track the duration of prolactin levels within the reference values after 1 and 3 months of treatment. Women were divided into three groups: the first group, where cabergoline with plasmapheresis was used, the second group patients used cabergoline with ozone therapy, and the third group patients had only drug therapy. Results and discussion. Discrete plasmapheresis was carried out in the first phase of the cycle every other day. Ozone therapy was carried out in the form of intravenous drip infusions of ozonized physiological saline. After 3 months, prolactin levels were re-analyzed and it was reliably determined that group 1 and 2 had a lower prolactin concentration than group treated with drug therapy alone. Namely, in group 1 women prolactin remained decreased by 66.1 % (р <0.05), compared with the initial level, and in the second group it was by 62.92 % (р <0.05), in group 3 it was by 36.98 % (p<0.05). Comparing the results of the 1st and 3rd months of treatment, groups 1 and 2 maintained a more stable level of lactotrophic hormone than those in group 3. All the above indicate a greater efficacy of complex therapy and a prolonged effect, which may increase the percentage of positive prognosis after treatment, namely to increase the rate of pregnancy in such patients, which is in line with the current literature. Conclusion. The study showed that the integrated use of non-drug treatment methods affected the preservation of prolactin levels within the reference values for a longer time, as evidenced by the results of blood serum analysis. This significantly increases the positive prognosis of pregnancy quality in patients with functional hyperprolactinemia.
Применение комплексной терапии лечения синдрома гипепролактинемии
Applying Complex Therapy at Treatment of Hyperprolactinemia
Keywords: пролактин; гіперпролактинемія; безпліддя; гиперпролактинемия; бесплодие; prolactin; hyperprolactinemia; infertility